The Association between D-Dimer and Prognosis in the Patients with Oral Cancer - Kenji Yamagata; Satoshi Fukuzawa; Naomi Ishibashi-Kanno; Fumihiko Uchida; Toru Yanagawa; Hiroki Bukawa (MDPI AG, 2020)
D-dimer levels are reported to relate with tumor stage, prognosis, and lymph node involvement, as well as overall survival (OS) in patients with solid tumors. The purpose of this study was to investigate association between the value of D-dimer and the prognosis of oral cancer (OC). We designed a retrospective cohort study and enrolled a sample of patients who were diagnosed with OC and treated with surgery and/or radiotherapy. The predictor was the D-dimer and outcome variable was OS. Other variables included age, neutrocyte count, neutrophil lymphocyte ratio (NLR), C-reactive protein (CRP), and management. Differences in OS rate were analyzed by log-rank test. A Cox proportional hazards model was used to adjust for the effects of potential confounders. Differences with a P value less than 0.05 were considered statistically significant. In 88 patients with OC, D-dimer median value for the predicting OS was 0.7 µg/mL. There was a significant difference in OS when patients were stratified according to D-dimer, with an OS rate of 77.8% for patients with low D-dimer (<0.7), and 57.3% with high D-dimer (≥0.7) (p = 0.035). Univariate analyses revealed close correlations between OS and age, neutrocyte count, NLR, CRP, and D-dimer (<0.7 and ≥0.7). Cox multivariate analysis identified management (mainly surgery vs. radiotherapy) (HR 3.274, 95% CI 1.397-7.676; p = 0.006) as independent predictive factors for OS. There was a significant difference in OS when patients were stratified according to D-dimer with low (<0.7) and high D-dimer (≥0.7) (p = 0.035). Though, as a predictive factor, management was associated with OS.